2007
DOI: 10.1111/j.1439-0264.2007.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Number of Coronary Ostia in Syrian Hamsters (Mesocricetus auratus) with Normal and Anomalous Coronary Arteries

Abstract: Little attention is being paid to the presence of accessory coronary artery ostia in man and non-human mammals due to their limited clinical relevance. However, information about their frequency and the cardiac territories irrigated by the vessels arising from them is of interest to obtain an accurate survey of the establishment of the coronary artery system in each species. The aim here was to compare the incidence and significance of the accessory coronary ostia in Syrian hamsters with normal coronary arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The presence of additional coronary ostia in mammals appears to be relatively frequent. A separate ostium leads to conal artery in 33–51% of studied human patients, 50% of common squirrel monkeys or 8% of pigs (Durán et al., ). In a series of studies considering the normal morphology of the aortic valve, the presence of accessory coronary ostia was found in 148 individuals of 2829 Syrian hamsters ( Mesocricetus auratus ) studied (Cardo et al., ; Durán et al., ,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of additional coronary ostia in mammals appears to be relatively frequent. A separate ostium leads to conal artery in 33–51% of studied human patients, 50% of common squirrel monkeys or 8% of pigs (Durán et al., ). In a series of studies considering the normal morphology of the aortic valve, the presence of accessory coronary ostia was found in 148 individuals of 2829 Syrian hamsters ( Mesocricetus auratus ) studied (Cardo et al., ; Durán et al., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…A separate ostium leads to conal artery in 33–51% of studied human patients, 50% of common squirrel monkeys or 8% of pigs (Durán et al., ). In a series of studies considering the normal morphology of the aortic valve, the presence of accessory coronary ostia was found in 148 individuals of 2829 Syrian hamsters ( Mesocricetus auratus ) studied (Cardo et al., ; Durán et al., ,b). In other studies using fewer animals, the presence of a third coronary artery (TCA) arising from the right aortic sinus was found in 2% of African green monkeys ( Cercopithecus aethiops ) and long‐tailed macaques ( Macaca fascicularis ) studied (Nikolić et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This also happened in this kangaroo; however we must add the presence of a different ostium for the septal artery. The septal artery arose from a separate ostium in 4.8% of the Syrian hamsters (Duran et al, 2007). It can be concluded that in the two kangaroo studied, the separate origin of the septal artery cannot be considered a coronary anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…For a better understanding of our observations, it should be noted that in the Syrian hamster, the normal coronary artery pattern is characterized by the presence of two intramyocardial coronary arteries, right and left (Sans‐Coma et al., 1993; Durán et al., 2005, 2007). The right coronary artery originates from the right aortic sinus when the aortic valve is tricuspid (Fig.…”
Section: Methodsmentioning
confidence: 98%
“…This latter vessel can be considered physiologically equivalent to the left anterior descending artery of humans and the paraconal inter‐ventricular artery of non‐human mammals having subepicardial coronary arteries. The inter‐ventricular septum is basically supplied by the so‐called septal artery, which arises from a separate ostium in about 5% of cases, thus behaving as a third coronary artery in the Syrian hamster (Durán et al., 2007).…”
Section: Methodsmentioning
confidence: 99%